Pemberdayaan Ibu Rumah Tangga dalam Melakukan Manajemen Gizi Keluarga - Rini Handayani; Leza Fidyah Restiana; Namira Wadjir Sangadji; Kartini; Mugi Wahidin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Based on interviews with the Head of RT 001/RW 015 in Karang Tengah Village, health problems identified among children in the area include diarrhea, upper respiratory tract infections, tuberculosis, dengue fever, malnutrition, and typhoid fever. One contributing factor is poor nutritional management at the family level. Mothers serve as the primary managers within the household, yet many lack sufficient knowledge regarding family nutrition management. This community service activity was carried out through health education lectures and focus group discussions (FGDs). The lecture sessions covered nutritional intake, family nutrition management, and the consequences of poor nutritional practices, supported by PowerPoint presentations. The FGDs guided participants in developing daily family menus based on balanced nutritional standards using provided worksheets. Pre-test and post-test assessments were conducted to evaluate effectiveness. Results showed an increase in respondents' scores following the activity, with the largest increase observed in the question on the Pillars of Balanced Nutrition, rising from 14.3% to 54.8%. Similar activities are recommended to be conducted regularly, with more time allocated for simulation sessions to better support mothers in applying family nutrition management.